Nervonic acid alleviates radiation-induced early phase lung inflammation by targeting macrophages activation in mice - Wang, Chenlin; Wu, Yanan; Liu, Chao; Li, Yang; Mi, Song; Yang, Xiaofan; Liu, Tong; Tian, Yuanjing; Zhang, YingYing; Hu, Pingping; Qiao, Lili; Deng, Guodong; et al. (Frontiers in Immunology, 2024)
BackgroundPatients receiving chest radiation therapy, or exposed to high radiation levels due to accidental nuclear leakage are at risk of radiation-induced lung injury (RILI). In innate immunity, macrophages not only exhibit certain radiation tolerance but also play an important regulatory role in the whole pathological process. Nervonic acid (NA), a long-chain unsaturated fatty acid found in nerve tissue, plays a pivotal role in maintaining normal tissue growth and repair. However, the influence of NA on RILI progression has yet to be examined.AimThis study aimed to assess the role of macrophage subtypes in RILI and whether NA can alleviate RILI. Specifically, whether NA can alleviate RILI by targeting macrophages and reducing the levels of inflammatory mediators in mouse models was assessed.MethodsMice RILI model was employed with 13 Gy whole thoracic radiation with or without administration of NA. Various assays were performed to evaluate lung tissue histological changes, cytokine expression, IκB-α expression and the number and proportion of macrophages.ResultsRadiation can lead to the release of inflammatory mediators, thereby exacerbating RILI. The specific radiation dose and duration of exposure can lead to different dynamic changes in the number of subpopulations of lung macrophages. NA can affect the changes of macrophages after irradiation and reduce inflammatory responses to alleviate RILI.ConclusionMacrophages play a significant role in the integrated pathological process of lung injury after irradiation which shows a dynamic change with different times. NA can protect lung tissues against the toxic effects of ionizing radiation and is a new potential functional component for targeting macrophages.